PERANAN PENYIDIK DALAM TINDAK PIDANA PEMILIHAN KEPALA DAERAH - Rusmanto Rusmanto (Jurnal Hukum, 2019)
This research is about: The Role of the Police Investigators Handling Crime Election, aims to identify and analyze the role of police investigator in the handling of criminal acts in the elections. barriers faced by investigators in handling criminal acts of the local elections and how to overcome them. The method used juridical empirical. Data collected through interviews, documents and literature studies. The data were analyzed qualitatively. Police investigators role in the handling of criminal acts Selection of regional heads, namely as an investigator of the alleged criminal acts of the local elections. Handling of criminal acts carried out by the local election supervisory committee report after a discussion of the integrated role in law enforcement centers to report violations of the elections. There is a problem in penangana criminal election among other issues Money, Criminal policies should be done in full against certain acts, especially against a weak special crimes if applied to the Criminal Code which is the general criminal provisions, as well as the election of the offenses in addition to regulate acts that may be liable to criminal threat should be listed as well. It is important that the criminal policy can achieve the desired objectives. There should be attempts non penal more intensive in combating criminal election as money politics that still exists due to the weak criminal sanctions.